The determinants of sickness presenteeism - Palo, Sasmita; Pati, Sucha (2013)
Sickness presenteeism refers to attending work while ill. This article replicated some of the existing results relating to presenteeism as well as evidenced new hypotheses that have only been hinted in the literature. It examined effects of three broad categories of determinants i.e. work related, personality related and personal circumstances of an individual on presenteeism. A major addition in this study was inclusion of personality factors in predicting Sickness presenteeism. It is contended that presenteeism has important implications for organizational theory and practice, and presents a research agenda for organizational scholars. - Reproduced.
Keywords: Sickness